Urachal mucinous adenocarcinoma in the pelvic wall mimicking endometriosis - Saida, Tsukasa (Radiol Case Rep, 2018)
We report the case of a 30-year-old woman who complained of a painful palpable mass. Magnetic resonance imaging revealed an ill-defined mass approximately 8 cm in diameter with internal microcytic components. The mass diffusely involved the subcutaneous tissues, the muscles of the pelvic wall, and urinary bladder via a postoperative scar and resembled endometriosis. The histopathologic diagnosis was mucinous adenocarcinoma arisen from the urachal remnant. This is a very rare case of urachal adenocarcinoma arising mainly in the pelvic wall and mimicking endometriosis on MRI.